Attributable risk factors for asymptomatic malaria and anaemia and their association with cognitive and psychomotor functions in schoolchildren of north-eastern Tanzania. - Geofrey Makenga; Vito Baraka; Filbert Francis; Daniel T R Minja; Samwel Gesase; Edna Kyaruzi; George Mtove; Swabra Nakato; Rashid Madebe; Sif R Søeborg; Kathrine H Langhoff; Helle S Hansson; et al. (PLoS ONE)
In Africa, children aged 5 to 15 years (school age) comprises more than 50% (>339 million) of the under 19 years population, and are highly burdened by malaria and anaemia that impair cognitive development. For the prospects of improving health in African citizens, understanding malaria and its relation to anaemia in school-aged children, it is crucial to inform targeted interventions for malaria control and accelerate elimination efforts as part of improved school health policy. We conducted a study to determine the risk factors for asymptomatic malaria and their association to anaemia. We explored the prevalence of antimalarial drug resistance as well as the association of asymptomatic malaria infection and anaemia on cognitive and psychomotor functions in school-aged children living in high endemic areas. This study was a comprehensive baseline survey, within the scope of a randomised, controlled trial on the effectiveness and safety of antimalarial drugs in preventing malaria and its related morbidity in schoolchildren. We enrolled 1,587 schoolchildren from 7 primary schools located in Muheza, north-eastern Tanzania. Finger-pricked blood samples were collected for estimation of malaria parasitaemia using a microscope, haemoglobin concentration using a haemoglobinometer, and markers of drug resistance processed from dried blood spots (DBS). Psychomotor and Cognitive functions were assessed using a '20 metre Shuttle run' and a test of everyday attention for children (TEA-Ch), respectively. The prevalence of asymptomatic malaria parasitaemia, anaemia and stunting was 26.4%, 49.8%, and 21.0%, respectively with marked variation across schools. In multivariate models, asymptomatic malaria parasitaemia attributed to 61% of anaemia with a respective population attribution fraction of 16%. Stunting, not sleeping under a bednet and illiterate parent or guardian were other factors attributing to 7%, 9%, and 5% of anaemia in the study population, respectively. Factors such as age group (10-15 years), not sleeping under a bednet, low socioeconomic status, parents' or guardians' with a low level of education, children overcrowding in a household, and fewer rooms in a household were significantly attributed to higher malaria infection. There was no significant association between malaria infection or anaemia and performance on tests of cognitive function (sustained attention) or psychomotor function (VO2 max). However, a history of malaria in the past one month was significantly associated with decreased cognitive scores (aOR = -4.1, 95% CI -7.7-0.6, p = 0.02). Furthermore, stunted children had significantly lower VO2max scores (aOR = -1.9, 95% CI -3.0-0.8, p = 0.001). Regarding the antimalarial drug resistance markers, the most prevalent Pfmdr1 86-184-1034-1042-1246 haplotypes were the NFSND in 47% (n = 88) and the NYSND in 52% (n = 98). The wild type Pfcrt haplotypes (codons 72-76, CVMNK) were found in 99.1% (n = 219) of the samples. Malaria, stunting and parents' or guardians' illiteracy were the key attributable factors for anaemia in schoolchildren. Given malaria infection in schoolchildren is mostly asymptomatic; an addition of interventional programmes such as intermittent preventive treatment of malaria in schoolchildren (IPTsc) would probably act as a potential solution while calling for an improvement in the current tools such as bednet use, school food programme, and community-based (customised) health education with an emphasis on nutrition and malaria control.